The role of biology curriculum in promoting student health, environmental awareness, and academic success: Teacher responsibilities - Bara, Enkelejda; Bara, Gezim; Pupe, Sara (Edelweiss Applied Science and Technology, 2024)
The biology curriculum significantly shapes students’ understanding of health and environment, equipping them with knowledge and skills necessary for responsible citizenship and informed decision-making. This study aims to examine how the biology curriculum affects students' education, focusing on how it helps students become more aware of health and environmental issues. The study utilized a mixed-methods research design. A Purposive sampling was utilized for this research. The study was carried out in four schools in Tirana: Gymnasium “Aleks Buda, “Gymnasium “Samiu,” Gymnasium “Isa Boletini,” and Gymnasium “Partizani.” The sample consists of 200 students and 20 teachers. The research instruments used for the collection of data were questionnaires, interviews, and classroom observation. Findings of the study show that students’ understanding of essential health-associated subjects was greatly improved by their participation in the biology class. It also highlights how important it is for teachers to raise students' achievement levels. The study shows the important role instructors play in fostering an encouraging and exciting atmosphere for education. Furthermore, instructors may pinpoint how to meet every student's distinctive educational requirements with customized supervision, offering individualized assistance along with helpful criticism. In conclusion, the curriculum acts as a catalyst for bringing important health issues, like disease prevention and individual well-being, to the public's attention while simultaneously encouraging a sense of responsibility for the sustainability of the environment and the preservation of our world.